Aging and positivity : a cognitive comparison of encoding and memory retrieval in two different age groups : a thesis presented in partial fulfillment of the requirements for the degree of Master of Science in Psychology at Massey University - Bryce, Barbara Jane (Massey University, 2007)
The positivity effect refers to a developmental trend in which the ratio of positive over negative events becomes more pronounced over the lifespan, suggesting that older adults evaluate, encode and retrieve stimuli from recall differently from young adults. Previous research has focused on identifying the positivity effect, on whether memory distortion has caused it, and for how long older adults can maintain positive emotion. The aim of this experiment was to investigate the cognitive functions behind the positivity effect. It examined differences in the encoding and memory retrieval of neutral, positive and negatively valenced images in young and old adults by comparing measures of self-reported intensity of arousal in 30 females aged 18-30 with 30 females aged 65-80. A slideshow of 60 valenced images from the International Affective Picture System was shown in either a direct emotion or an indirect emotion task, followed by a brief interference task, after which all participants were rated on the accuracy of their recognition of the valenced images. Results revealed that older adults had a positivity effect in most tasks when compared with younger adults, enhanced by a diminished preference for negative images. Psycho-social implications of this positively-biased view of themselves and the world include concerns over personal health care and safety issues related to independent living.
Keywords: Memory -- Age factors; Older people -- Psychology; Emotions and cognition